Improvement of Concrete Durability by Nanomaterials. (2015) - Saloma; Nasution, Amrinsyah; Imran, Iswandi; Abdullah, Mikrajuddin
Abstract: The green concrete capable for sustainable development is characterized by application of industrial wastes to reduce pollution of the environment. Fly ash processed with nanotechnology developed by Indonesia Center for Ceramics using Polishing Liquid Milling Technology. Nanomaterial concrete is new generation concrete formed of materials of the grain size of nanoscale. The materials used in this research were cement type I, nanosilica 10 - 150 nm, quartz powder in 0.3 - 25.0 μm, fine sand (quartz of sand) size of 50 - 650 μm, coarse aggregate in 5 - 10 mm, and superplasticizer. In this paper, mechanisms are discussed by which the incorporation of nanomaterials in concrete enhances durability to sulfate attack. Application of nanotechnology is an effective way to reduce environment pollution and improve durability of concrete. For countries like Indonesia, this technology can play an important role in meeting the huge demand for infrastructure in a sustainable manner.